Ultra-efficient polymer binder for silicon anode in high-capacity lithium-ion batteries. (July 2020) - Gao, Shilun; Sun, Feiyuan; Brady, Alexander; Pan, Yiyang; Erwin, Andrew; Yang, Dandan; Tsukruk, Vladimir; Stack, Andrew G.; Saito, Tomonori; Yang, Huabin; Cao, Peng-Fei
Abstract: As a highly promising anode material for high-capacity lithium-ion batteries (LIBs), the low electronic conductivity and large volume variation of silicon (Si) make the slurry-coating Si based electrode requiring high content of "inert" materials and suffering rapid capacity fading. Herein, a polyimine, synthesized via one-step condensation reaction, has been demonstrated as an ultra-efficient polymer binder that can resolve the above issues. The polyimine binder containing Si electrode delivers superior electrochemical performance: a delithiation specific capacity of 804.4 mAh g −1 with capacity retention of 82.4% after 1000 cycles at the current density of 2 A g −1 . The high efficiency of polyimine binder for Si electrode has also been demonstrated with ultrahigh weight ratio of "active" material to "inert" material (RA/I ). The electrode with 95 wt% of Si (95Si/Polyimine, RA/I = 19) reveals a reversible delithiation capacity of 2114 mAh g −1 (capacity retention 80.4%) over 200 cycles at the current density of 400 mA g −1 . Even at the high current density of 2 A g −1, a delithiation capacity of 1087.8 mAh g −1 after 500 cycles can be obtained. Molecular simulations and atomic force microscopy (AFM) indentation are utilized to investigate the ultra-efficiency of polyimine binder. With simple manufacturing process and ultra-efficient binder performance, the designed polyimine binder will be definitely meaningful in achieving low-cost and high-capacity LIBs with prolonged cycle life. Graphical abstract: An ultra-efficient polymer binder enables the slurry-coated Si electrode with unprecedented highest weight ratio of "active" materials to "inert" materials (RA/I ) and prolonged cycle life is reported. Traditional Si based electrodes always require high content of "inert" materials and suffer rapid capacity fading. A polyimine, synthesized via one-step condensation reaction, can efficiently resolve the above issues, and the electrochemical performance of Si electrodes can be significantly improved using a small amount of polyimine binder. Molecular simulations and atomic force microscopy (AFM) indentation are utilized to investigate the ultra-efficiency of polyimine binder, and the current design will be useful in achieving the Si (or Si composite) electrodes with high cost efficiency and long cycle life. Image 1 Highlights: An ultra-effcient polymer binder for high-performance Si anode. Silicon electrode with unprecedented highest weight ratio of "active/inert" materials. Significantly improved binder performance than state-of-art binders. Towards a cost-efficient process and energy-efficient battery via developed polyimine binder.